Does previous participation in high-impact training result in residual bone gain in growing girls? One year follow-up of a 9-month jumping intervention - Kontulainen, S. A.; Kannus, P. A.; Pasanen, M. E.; Sievanen, H. T.; Heinonen, A. O.; Oja, P.; Vuori, I. (International Journal of Sports Medicine, 2002)
The skeletal response to exercise and training on bone is exceptionally good during the growing years. However, it is not known whether the benefit of training on bone is maintained after the training. This 20-month follow-up study assessed the effect of a 9-month jumping intervention on bone gain and physical performance in 99 girls (mean age 12.5 +/- 1.5 years at the beginning of the study) one year after the end of the intervention. Both bone mineral content (BMC), by dual energy X-ray absorptiometry (DXA) at the lumbar spine and proximal femur, and physical performance parameters (standing long jump, leg extension strength, and shuttle run tests) were measured at baseline and at 20 months. A multivariate regression analysis was first used to determine the best predictors of the BMC accrual by time. Analysis showed that age at baseline and square of age, changes in height and weight, and pubertal development into Tanner stages 4 and 5 during the follow-up explained the majority of the BMC gain. Then, the effect of participation in the 9-month exercise intervention on BMC accrual and physical performance was analysed adding this variable (participation: yes/no) into the model. The regression analysis showed that the trainees (N = 50) had 4.9 % (95 % CI, 0.9 % to 8.8 %, p = 0.017) greater BMC increase in the lumbar spine than the controls (N = 49). The mean 20-month BMC increase in the lumbar spine was 28 % (SD 19) in the trainees compared to 22 % (12) increase in the controls. In the proximal femur, the trend was similar but the obtained 2 to 3 % higher BMC accrual in the trainees (compared to that in controls) were statistically insignificant. Among the performance variables, using the same model that best predicted the BMC accrual, the only statistically significant between-groups difference, in favour of the trainees, was the improvement in the standing long jump test (6.4 %, 95 % CI, 2.3 % to 10.4 %, p = 0.002). Improvements in the leg extension strength and shuttle run tests showed no between-groups difference. In conclusion, although the greatest proportion of bone mineral accrual in growing girls is attributable to growth, an additional bone gain achieved by jumping training is maintained at the lumbar spine at least a year after the end of the training.